(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article describes in detail about the prism, its types and properties, the face and size of the prism surface, the perpendicular section of the prism, the edges and sides of the prism, the segment of the sphere and the circle of the sphere, the volume of the sphere and its parts.